If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4a + 8 = 4a Reorder the terms: 8 + -4a = 4a Solving 8 + -4a = 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 8 + -4a + -4a = 4a + -4a Combine like terms: -4a + -4a = -8a 8 + -8a = 4a + -4a Combine like terms: 4a + -4a = 0 8 + -8a = 0 Add '-8' to each side of the equation. 8 + -8 + -8a = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -8a = 0 + -8 -8a = 0 + -8 Combine like terms: 0 + -8 = -8 -8a = -8 Divide each side by '-8'. a = 1 Simplifying a = 1
| 5x^2-14x-13=0 | | -6(5r+15)=600 | | 4x^2+4x-60=0 | | X^2-23x+22=0 | | S=.2(300-50) | | -21+5r=54 | | 2c(7c+5)=0 | | A^2-3ab-28b^2=0 | | -3a+9=3a | | 65=.2(w-40) | | (w+9)(w-15)=0 | | 13xy+18xy-20xy= | | 65=.2(w-10)4 | | 1+5y=8x-20 | | 4x+6x-17=2(2x+3x) | | -y+124=30 | | 9a+2=20 | | -t*42=3 | | 4a+12=4 | | -10m-8m=-24 | | 14/1+6/3 | | 1/2(6m-10)=3m-5 | | 27b+12b= | | 35=.2(255-10e) | | 3x+6=27+3 | | -1.1428x-6=-2.6x-14 | | (x+1)(x-1)(x-3)(x-6)=0 | | 6=-9-6 | | 51-7x=12+(-4x) | | 2x+3+5x=13 | | 5+3(n+9)=-3 | | 5+x-3[x+4]=-17 |